Merajut Hidup Bahagia dan Bermakna pada Lansia melalui Reminiscence Therapy - Ratna Mustika Handayani (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
The elderly have many decreased abilities in many aspects of their development, therefore they have limitations in their activities and social interactions in meeting their needs. Those limitations make the elderly feel useless and worthless which may evoke anxiety, stress, and even depression. This study aims to determine the process and the advantages of reminiscence therapy in increasing the happiness and meaning in life in elderly people. The method used in this empirical investigation was literature study, namely by filtering several published scientific articles which are related to the topic of this study. 72 articles relevant and published between 2012 and 2022 were found. The result of the literature study shows that reminiscence therapy is a therapeutic process that guides elderly people to review their past positive and negative experiences, and then they interpret and take lesson from all those events to build a positive view and acceptance towards themselves. This will be able to increase the happiness and meaning in life in the elderly until ego integrity is achieved.Keywords: Elderly, Happiness, Meaning in life, Reminiscence Therapy.